2019
DOI: 10.1093/oep/gpz066
|View full text |Cite
|
Sign up to set email alerts
|

Identifying price-leadership structures in oligopoly

Abstract: Oligopoly can give rise to complex patterns of price interaction and adjustment. While oligopolistic firms may divide into price leaders and price followers, it is conceivable that some may take on dual roles, being a leader to one group but a follower to a different group in a hierarchical structure. The contribution of this article is to show how such dual relationships are possible in theory along with providing an empirical method to help identify price-leadership structures in n-firm oligopoly. As an illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We mainly referred to the UK grocery market, in which suppliers and sellers negotiate their input prices and where recent empirical evidence by Seaton and Waterson (2013) and Kim et al (2019) has shown that the downstream market competition has a price leadership structure.…”
Section: Escrihuela-villar and Ferraresementioning
confidence: 99%
See 4 more Smart Citations
“…We mainly referred to the UK grocery market, in which suppliers and sellers negotiate their input prices and where recent empirical evidence by Seaton and Waterson (2013) and Kim et al (2019) has shown that the downstream market competition has a price leadership structure.…”
Section: Escrihuela-villar and Ferraresementioning
confidence: 99%
“…In particular, Inderst and Valletti (2009) state: "Our own observations suggest, however, that at least in the UK grocery industry, linear pricing is prevalent in the cases of fresh produce, milk and bakery products." Moreover, in line with the empirical evidence provided by Kim et al (2019), we let the high capacity firm behave as the price leader and the low capacity firm behave as the price follower.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations